Functional neural correlates of non-verbal ability in 5-year old children: a FinnBrain Birth Cohort study - Puustinen, Petra (My University, 2025)
Non-verbal cognitive ability has a broad and significant impact on an individual's entire life. As reported by previous research, higher cognitive abilities and non-verbal intelligence are associated with better life performance and improved parie-to-frontal connectivity. The aim of the study was to investigate the relationship be-tween non-verbal cognitive abilities and brain function in 5-year-old children. We explored the associations between non-verbal cognitive ability and brain func-tion especially in the parieto–frontal integration theory (P–FIT) model regions in 82 5-year-old children from the FinnBrain Cohort Study. Task-free functional magnetic resonance imaging (fMRI) was acquired at the age of 5 years. Non‐verbal cognitive ability was measured using the Performance Intelligence Quotient (PIQ) estimated from the Block Design and Matrix Reasoning subtests from the Wechsler Preschool and Primary Scale of Intelligence (WPPSI‐III). The relation between non-verbal cog-nitive ability and brain function was assessed using regional homogeneity (ReHo), amplitude of low-frequency fluctuations (ALFF), and independent component analy-sis (ICA) maps.We found no associations between non-verbal ability and brain function in a task-free state at the age of 5 years. This study provides preliminary evidence on the development of connectivity in the brain for future research, and highlight the need for further investigation into the re-lationship between cognition and brain networks in young children.
Keywords: functional magnetic resonance imaging, cognitive ability, children